Russia's Participation in the International Export of Capital - A. S. Bulatov (Vestnik MGIMO-Universiteta)
The article analyses the export of capital from Russia in the international export of capital, primarily from emerging market countries, especially countries BRIСS. An attempt is made to reveal the characteristic features of the Russian model of export of the capital, its impact on the internal economic processes and the possibilities of its regulation.